PENGARUH KEMUDAHAN PENGGUNAAN APLIKASI MOBILE FORE COFFEE TERHADAP MINAT BELI KONSUMEN FORE COFFEE (Survei pada followers Instagram Fore Coffee) - Arghy Farhan Dhia (2020)
This study discusses the influence of the ease of use of the Fore Coffee mobile application to the consumer buying interest of Fore Coffee. The purpose of this study was to determine whether there is an influence of the ease of use of the Fore Coffee mobile application to the buying interest of Fore Coffee consumers, and to find out how much influence. The theory used in this study is the Theory of Uses and Gratification. The method used is a quantitative research method. Data collection is done by distributing questionnaires. The population in this study was Instagram Fore Coffee followers, which were then obtained by 100 respondents. The sampling technique used in this study is the non probability sampling technique. Data processing in this study uses SPSS version 26. Based on the results of the calculation of the coefficient of determination obtained the effect of ease of use of mobile applications on buying interest of 47.8%, while the remaining 52.2% is the influence of other variables not examined in this study. The results of testing the hypothesis using the t test showed that t arithmetic 9,467> t table 1,664, it can be concluded that H0 was rejected and Ha was accepted. R value obtained through the correlation test of 0.691 which is in the category of interpretation of the correlation coefficient indicates a strong level of influence. So, it can be known and concluded that the ease of use of the Fore Coffee mobile application has a strong influence on the buying interest of Fore Coffee consumers on Fore Coffee followers.